Serum C-reactive protein levels are associated with clinical pregnancy rate after in vitro fertilization among normal-weight women - Zhang, Huixia; Li, Xin; Zhang, Fan; Li, Fei; Jin, Haixia; Su, Yingchun; Li, Gang (Frontiers in Endocrinology, 2023)
Objective: To assess whether low-grade inflammation, measured by serum high-sensitivity C-reactive protein (hsCRP) levels, is associated with IVF outcomes. Design: A retrospective study. Setting: University-affiliated in vitro fertilization center. Patient(s): In this study, 875 normal-weight women who underwent their first fresh embryo transfer (ET) cycles for IVF treatment were divided into three groups according to serum concentrations of hsCRP. Intervention(s): Serum from women undergoing IVF was collected on day 2-4 of a spontaneous menstrual cycle before commencing ovarian stimulation. Main Outcome Measure(s): The IVF outcomes include implantation, biochemical pregnancy, clinical pregnancy, miscarriage and live birth rates. Result(s): Cycles were divided into three groups according to the baseline serum concentrations of hsCRP: low hsCRP (<0.66 mg/L; n=360), middle hsCRP (0.66–2 mg/L; n= 360), high hsCRP (≥2.0 mg/L; n=155). Maternal age was similar among three groups. High hsCRP group had higher BMI compared with the other two groups. The protocol of controlled ovarian hyperstimulation, gonadotropin dose administered, the serum estradiol, progesterone and the endometrial thickness on the day of triggering, the number of retrieved oocytes, fertilized oocytes and good quality embryos, and the oocyte maturation rate were similar among three groups. Implantation, biochemical pregnancy and clinical miscarriage rates were not significantly different among three groups. Clinical pregnancy rate was significantly lower in the high hsCRP group (51.6% versus 63.3%, respectively; P<0.0167), which contributed to a significant decrease in live birth rate (40.6% versus 53.3%, 40.6% versus 52.2%, respectively; P<0.0167). High serum hsCRP levels and maternal age were found to influence the frequency of live birth. Conclusion(s): Among normal-weight women undergoing their first IVF treatment, we found that systemic, low-grade inflammation is associated with reduced clinical pregnancy and live birth rates after fresh ET cycles.